2010
DOI: 10.2478/s11536-010-0043-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gingival blood flow during orthodontic treatment

Abstract: AbstractThe aim of the study was to investigate the changes in gingival blood flow due to orthodontic forces. Eleven volunteers, with the maxillary canine in an ectopic position were tested. A Laser Doppler Flowmeter (LDF) with a gingival probe was used, registering both the blood flow and temperature of the gingivae. After baseline measurement, a fixed orthodontic appliance was bonded. Measurements were repeated monthly, after activation of the appliance. The study lasted 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…They observed that in most patients, the first values decreased (during the first month) and then increased gradually up to the sixth month. Our results coincide with those of Barta et al because, in our study, we observed an increase in gingival perfusion at all of the time intervals with different arches [ 29 ]. The vascular morphology is related to blood flow changes (relaxation and contraction), and these changes may be the first sign of the onset of pathological events; therefore, it is helpful to provide information related to blood flow in clinical practice.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…They observed that in most patients, the first values decreased (during the first month) and then increased gradually up to the sixth month. Our results coincide with those of Barta et al because, in our study, we observed an increase in gingival perfusion at all of the time intervals with different arches [ 29 ]. The vascular morphology is related to blood flow changes (relaxation and contraction), and these changes may be the first sign of the onset of pathological events; therefore, it is helpful to provide information related to blood flow in clinical practice.…”
Section: Discussionsupporting
confidence: 93%
“…Researchers have reported that Nitinol arches produce constant and continues forces to generate greater tooth movement in comparison to stainless steel arches; this could be a possible explanation for the increase in the gingival perfusion of these arches [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For assessment of tissue vascularity at the level of microcirculation, laser Doppler Flowmetry (LDF) is an appropriate method (37).This method has been used for the detection of blood flow in oral mucosal, pulpal, muscular and gingival tissues (38,39,40,41,42,43,44).…”
Section: Bone Vascularitymentioning
confidence: 99%
“…The regression coefficient of decreased blood flow to the percentage of tooth displacement was significantly higher in young subjects than in adults [ 74 ]. Barta et al showed that the application of a force of 75 g to the maxillary canine in an ectopic position resulted in a decrease in gingival blood flow up to 50%, but it returned toward the baseline after a few months [ 75 ].…”
Section: Reviewmentioning
confidence: 99%